1994
DOI: 10.1002/pro.5560030806
|View full text |Cite
|
Sign up to set email alerts
|

Properties of a recombinant human hemoglobin double mutant: Sickle hemoglobin with Leu‐88 (β) at the primary aggregation site substituted by Ala

Abstract: A recombinant double mutant of hemoglobin (Hb), E6V/L88A(@), was constructed to study the strength of the primary hydrophobic interaction in the gelation of sickle Hb, Le., that between the mutant Val-6(0) of one tetramer and the hydrophobic region between Phe-85(/3) and Leu-88(/3) on an adjacent tetramer. Thus, a construct encoding the donor Val-6(@ of the expressed recombinant HbS and a second mutation encoding an Ala in place of Leu-88(@) was assembled. The doubly mutated 0-globin gene was expressed in yeas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Their results suggest that the relative order for polymerization of the b85 mutants of Hb S depends on amino acid hydrophobicity (Leu > Phe > Ala > Thr > Trpb85). Using a similar yeast-expression system, de Llano & Manning (1994) investigated the role of b88Leu in Hb S polymerization by constructing a mutant of Hb S, r Hb (b6Glu : Val, b88Leu : Ala). They found that the strength of the hydrophobic interaction between b6Val of one Hb S and b88Leu on an adjacent Hb S (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Their results suggest that the relative order for polymerization of the b85 mutants of Hb S depends on amino acid hydrophobicity (Leu > Phe > Ala > Thr > Trpb85). Using a similar yeast-expression system, de Llano & Manning (1994) investigated the role of b88Leu in Hb S polymerization by constructing a mutant of Hb S, r Hb (b6Glu : Val, b88Leu : Ala). They found that the strength of the hydrophobic interaction between b6Val of one Hb S and b88Leu on an adjacent Hb S (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The three Hb S variants were subjected to DNA sequence analysis of the entire ␤-globin cDNA using site-specific primers and fluorescently tagged terminators in a cycle-sequencing reaction in which extension products were analyzed on an automated DNA sequencer (7,9). The mutated ␤-globin cDNA regions were then excised by XhoI digestion and subcloned back into the XhoI site of the expression vector pGS389 (4).…”
Section: Methodsmentioning
confidence: 99%
“…Refinements in our knowledge of the mechanisms of polymerization of deoxyHb S and the effects of molecular and cellular alterations that might prove useful in treating sickle cell disease have become possible with the advent of techniques such as site-directed mutagenesis for preparing selected mutant Hbs (13,14), recombinant Hbs having both the Val-␤6 (sickle) substitution and another chosen substitution (double mutants) (15), as well as the development of varieties of sickling transgenic mice (16,17). In each case, it is important to assess accurately the polymerization and sickling tendency obtained with the new Hb or mixture, yet these Hbs are generally available in very limited amounts.…”
Section: Discussionmentioning
confidence: 99%